Crystal structure and cation-anion interactions of potassium (Difluoromethanesulfonyl) (trifluorome thanesulfonyl)imide - Sánchez-Diez, Eduardo; Garcia, Lorena; Arcelus, Oier; Qiao, Lixin; San Felices, Leire; Carrasco, Javier; Armand, Michel; Martínez-Ibañez, Maria; Zhang, Heng (Frontiers in Chemistry, 2023)
Sulfonimide salts are of great interest for battery use thanks to their special properties including sufficient superior chemical/thermal stabilities, structural flexibility, etc. In particular, the hydrogen-containing sulfonimide (difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide anion [N(SO2CF2H) (SO2CF3)]−, DFTFSI−, stands out owing to its suppressed anion mobility and superior electrochemical properties. We herein report the structural analyses of potassium (difluoromethanesulfonyl)(trifluoromethanesulfonyl)imide K [N(SO2CF2H) (SO2CF3)], KDFTFSI by virtue of single crystal X-ray diffraction and computational approaches. Our results reveal that KDFTFSI crystallizes in a orthorhombic cell (space group: Pbcn) comprising of cationic and anionic layers, which is similar to the conventional sulfonimide salt, potassium bis(trifluoromethanesulfonyl)imide K [N(SO2CF3)2], KTFSI. Gas-phase density functional theory calculations show that the conversion from trans to cis DFTFSI− anions is hindered due to the presence of stabilizing intramolecular H-bonding interactions in the trans conformer; yet interaction with K+ substantially minimizes the energy difference between the two conformers due to the formation of strong tridentate K+ coordination with oxygen atoms in the cis KDFTFSI. This work is anticipated to provide further understanding on the structure-property relations of hydrogenated sulfonimide anions, and thus inspire the structural design of new anions for battery research.